2009
DOI: 10.4161/psb.4.2.7627
|View full text |Cite
|
Sign up to set email alerts
|

Function of α subunit of heterotrimeric G protein in brassinosteroid response of rice plants

Abstract: The alpha subunit of heterotrimeric G-proteins (G alpha) is involved in a broad range of aspects of the brassinosteroid (BR) response, such as the enhancement of lamina bending. However, it has been suggested from epistatic analysis of d1 and d61, which are mutants deficient for G alpha and the BR receptor BRI1, that G alpha and BRI1 may function via distinct pathways in many cases. In this study, we investigated further the genetic interaction between G alpha and BRI1. We report the analysis of transformants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…We cannot exclude the possibility that BR has other branched pathways, which are independent of GA biosynthesis and signaling, that promote cell elongation. Several studies have suggested that there is another BR signaling pathway independent of the BRI1 receptor, possibly involving components such as D1, BU1, and TAIHU DWARF1/ERECT LEAF1 (TUD1/ELF1) Oki et al, 2009b;Tanaka et al, 2009;Hu et al, 2013;Sakamoto et al, 2013). Interestingly, D1 has also been suggested to be involved only in the high-sensitivity response of GA (i.e., in response to low concentrations of GA) (Ueguchi- Tanaka et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that BR has other branched pathways, which are independent of GA biosynthesis and signaling, that promote cell elongation. Several studies have suggested that there is another BR signaling pathway independent of the BRI1 receptor, possibly involving components such as D1, BU1, and TAIHU DWARF1/ERECT LEAF1 (TUD1/ELF1) Oki et al, 2009b;Tanaka et al, 2009;Hu et al, 2013;Sakamoto et al, 2013). Interestingly, D1 has also been suggested to be involved only in the high-sensitivity response of GA (i.e., in response to low concentrations of GA) (Ueguchi- Tanaka et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, gpa1 and agb1 mutants are hyposensitive to BR [21,26,128,129,133] in BR promotion of seed germination [26,73], and in BR inhibition of hypocotyl and root elongation [26]. agb1 mutants are hyposensitive to methyl jasmonate (MeJA) inhibition of root elongation and seed germination [18].…”
Section: Physiological Function Of G Proteinsmentioning
confidence: 99%
“…Thus, the role of D1/RGA1 in BR signaling pathway might not be specific and D1/RGA1 could be the factor acting at a very upstream position of many different signaling pathways. Double mutant analysis between d1 and d61-7 also suggests that D1/RGA1 should be involved in an alternative BR signaling pathway independent of OsBRI1 (Oki et al, 2009). …”
Section: D1/rga1mentioning
confidence: 94%
“…Interestingly, in d1 mutant, OsBU1 is obviously less induced by BR, indicating OsBU1 is downstream of D1/RGA1 in BR response (Tanaka et al, 2009). As D1 and OsBRI1 have been implicated function independent of the upstream BR signaling pathways (Oki et al, 2009), OsBU1 could be regarded as a much downstream integrator of BR responses.…”
Section: Osbu1mentioning
confidence: 98%
See 1 more Smart Citation